Task-Based Language Teaching With a Semantic-Centred Pedagogic Grammar - Gray, James W.; Smithers, Ryan W. (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2019)
Task-based language teaching (TBLT) is well known for providing authentic opportunities for second and foreign language (L2) skill development. However, for many learners the use of traditional grammar within TBLT lacks the functional support necessary to create accurate and fluent L2 output. The current study replaced traditional grammar explanations with a semantic meaning-order approach to pedagogical grammar (MAP or MAP grammar) as a means to bridge the language in tasks to their function and thereby strengthen form-to-meaning understanding. The study combined TBLT and MAP grammar to look for changes in the complexity, accuracy, and fluency of 127 L2 learners’ writings. The results showed TBLT and MAP separately increased syntactic complexity, whereas the combination of the two provided gains in accuracy and fluency. This was achieved by systematically directing learners’ attention to a sequence of functional choices thereby simplifying necessary metalinguistic explanations.